Nature for Resilience? The Politics of Governing Urban Nature. (16th March 2023) - Tozer, Laura; Bulkeley, Harriet; Kiss, Bernadett; Luque-Ayala, Andrés; Palgan, Yuliya Voytenko; McCormick, Kes; Wamsler, Christine
Abstract : Transcending initial efforts to make cities "climate smart" by focusing on the potential of new technologies and infrastructural interventions, various actors are increasingly interested in deploying nature to help achieve urban resilience. In this context, rather than taking resilience as a given property of particular systems or entities, it is important to examine why, how, with what implications, and for whom resilience is being enacted. We examine how and why nature-based solutions are being mobilized as a means for governing the resilience of cities and what this means for the ways in which urban resilience is imagined and enacted by different actors. Recognizing that behind different approaches to resilience are diverse ways of valuing nature, we identify four value positions through which nature comes to be understood, given meaning, form, and purpose. Drawing on systematic document analysis and sixty-six interviews from Cape Town, Mexico City, and Melbourne, we discuss how these four value positions of nature are manifested in nature-based interventions for resilience, as well as the implications both for the politics of resilience interventions and the opportunities for enabling social benefit through nature-based solutions. We find that the integration of intrinsic values for nature opens opportunities for nature-based solutions to enable social benefits through an increased focus on the means through which they are implemented. We conclude that urban-nature-as-resilience interventions serve to embed values and the socionatures they produce within the city, creating fundamentally different consequences for the forms and politics of nature-based interventions designed to realize urban resilience.